Shaming for Tax Enforcement - Dwenger, Nadja; Treber, Lukas (Management Science, 2022)
We investigate company reactions to the threat of reputational losses. To do so, we leverage the introduction of a naming-and-shaming policy for tax debt enforcement in Slovenia in 2012. The policy was announced four months before its implementation, which allows us to separate responses to the threat of shaming from the responses to actual shaming. Our extensive administrative tax data cover taxes owed and paid for the universe of taxpayers in Slovenia. Based on a quasi-experimental research design, we document that corporations significantly reduce their tax debt in response to the threat of shaming, particularly in industries in which reputational concerns are likely to be important. Self-employed individuals also reduce their tax debt but to a lesser extent. The publication of the first naming-and-shaming list further reduced tax debt among shamed taxpayers. However, the effect of actual shaming is marginal compared with that of the threat of shaming and reduces quickly. Previously compliant taxpayers remained compliant throughout. This paper was accepted by Yan Chen, decision analysis. Funding: This work was supported by Deutscher Akademischer Austauschdienst [Grant 91537728/211483], Deutsche Forschungsgemeinschaft [Grant DW 75/1-1], and Norges Forskningsråd [Grant 314479]. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2021.4295 .